Parasite diversity in mallard: A cross sectional study on Anas platyrhynchos from Munshiganj, Dhaka (Bangladesh Journal of Zoology, 2019)
Among the 60 Anas platyrhynchos domesticus (32 males and 38 females), all the mallards were infested with Anaticola cassicornis and Lipeurus caponis. A. cassicornis displayed the peak intensity (15.5 ± 3.64) in female ducks. The lowest prevalence was of Colpocephalum turbinatum (25%) and found in male but the intensity was high (15 ± 2.23). Among the endoparasites, the highest prevalence was of Ascaridia galli (85.71%) found in female ducks and the lowest was in Echinostoma trivolvus (12.5%) found in male. The peak intensity was of Sobolevicanthus sp. (17.8 ± 2.34) in female following Echinostoma revolutum (17.33 ± 0.97). Ectoparasites were seen to infest all the seasons. But endoparasites were more prevalent in summer than the autumn and winter.Bangladesh J. Zool. 47(1): 121-128, 2019